Aportes terapéuticos relacionados con el movimiento corporal humano sobre la funcionalidad y calidad de vida del adulto mayor. Espacio alternativo del adulto mayor. Salinas. diciembre 2022 – abril 2023 - Pilamunga Guapisaca, Renny Alexander (2023)
EXECUTIVE ABSTRACT The present titling project called Therapeutic contributions related to human body movement on the functionality and quality of life of the elderly, alternative space for the elderly, Salinas, December 2022 - April 2023, has as Objective: To determine the therapeutic contributions (Playful Activities , I dance therapy) related to human body movement on the functionality and quality of life of the elderly, through the essential information obtained allows to assess the real situation in the face of this problem and propose necessary solutions that help the elderly Method: it is a quantitative investigation Due to the fact that all the data were obtained from the application of scales and a survey, scores were assigned that allowed determining the degree of functionality, body mobility and quality of life in the elderly of the DAYTIME GERONTOLOGICAL CARE CENTER "TENDER WAKE UP" of the Salinas Parish belonging to the Guaranda canton. Surveys were applied and evaluated with the Barthel Index and the scale of quality of life in older adults (ICV) to 30 older adults belonging to the Gerontological Center, in the same way the analysis method was applied through the Microsoft Excel and SPSS program making a multifactorial table with a relationship between the dependent variables studied, which characterized the information in a hierarchy of codes, memos and citations prior to the elaboration of a hermeneutical unit. Keywords: Therapeutic, Functionality, Quality of life, Older Adult.